Constitutional and administrative law - Barnett, Hilaire (London : Routledge, 2021)
"Hilaire Barnett's Constitutional and Administrative Law has consistently provided students with reliable, accessible and comprehensive coverage of the Public Law syllabus. Mapped to the common course outline, the 14th edition equips students with a thorough understanding of the UK constitution's past, present and future by analysing and illustrating the political and socio-historical contexts that have shaped the major rules and principles of constitutional and administrative law, as well as ongoing constitutional reform. This edition has been fully updated and includes discussion of the consequences of the United Kingdom's withdrawal from the European Union, including the impact on the legislative supremacy of Parliament and the relationship between EU and domestic law after departure. It also features discussion of the 2020 Coronavirus Act, with its implications for state power, and ahead of the forthcoming new SQE qualification, revised multiple choice questions on the Companion Website. Ideal for students studying constitutional and administrative law for the first time, this is an indispensable guide to the challenging concepts and legal rules in public law"--
Introducing constitutional law -- Sources of the constitution -- The rule of law -- The separation of powers -- The royal prerogative -- Parliamentary sovereignty -- Structure and institutions of the European Union -- European Union law and national law -- Central government -- Ministerial responsibility -- Devolution and local government -- The electoral system -- Introduction to the House of Commons -- The legislative process -- Scrutiny of the executive -- The House of Lords -- Parliamentary privilege -- The protection of human rights -- Freedom of expression and privacy -- Freedom of association and assembly -- State security -- Judges and the English legal system -- Judicial review : introduction, jurisdiction and procedure -- Grounds for judicial review I : the substantive grounds for judicial review -- Grounds for judicial review II : procedural impropriety -- Tribunals and inquiries -- Commissioners for administration : Ombudsmen.
Includes bibliographical references and index.
Keywords: Constitutional law -- Great Britain; Administrative law -- Great Britain